Bacterial profile and antimicrobial susceptibility pattern of asymptomatic urinary tract infections among pregnant women attending antenatal clinic at tertiary care hospital in central India - Dr. Namrata Pawar; Dr. Kalpana Sadawarte; Dr. Tukaram Prabhu K. (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: It is estimated that 2 to 10% of pregnant woman suffer from any form of urinary tract infections. These infections complicate up to 20% ofpregnancies and are responsible for the majority of ante-partum admissions to the maternal-fetal medicine units. Material and methods: It was a cross sectional study conducted in the Department of Microbiology, Peoples College of Medical Sciences & Research Center, Bhopal (M.P) during period of July 2015 to March 2016. A total of 210 pregnant women having asymptomatic bacteriuria during the period of July2015 to March 2016 attending antenatal clinic were included (all trimester) in this study. Results: Women in age group 21-30years showed the highest incidence of asymptomatic bacteriuria (70.58%), incidence of asymptomatic bacteriuria was generally high throughout pregnancy, but relatively highest during the second trimester. Escherichia coli was the most common 9 (52.94%) followed by Staphylococcus aureus 4 (23.52%), Klebisella pneumonia 2(11.76%) among the isolates. E.coli was found to be sensitive to cefepime and norfloxacin followed by ceftazidime ceftriaxone amoxicillin + clavulanic acid, nitrofurantoin, gentamycin and amikacin. Conclusion: This study revealed 8.09% prevalence of asymptomatic bacteriuria among pregnant women. This is of concern because UTI in pregnancy may have serious consequences for both the mother and the child.